Associated factors of suicidal ideation among older persons with dementia living at home in eight European countries - Cecilia Holmstrand; Ingalill Rahm Hallberg; Kai Saks; Helena Leino-Kilpi; Anna Renom Guiteras; Hilde Verbeek; Adelaida Zabalegui; Caroline Sutcliffe; Connie Lethin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Objectives: This study aimed to investigate the occurrence of suicidal ideation and associated factors in older persons with dementia living at home in eight European countries, and its association with quality of life. Furthermore, changes in suicidal ideation over time were investigated.
Methods: This cohort study (n = 1,223) was part of the European "RightTimePlaceCare" project conducted in 2010-2013. Participating countries were Estonia, Finland, France, Germany, the Netherlands, Spain, Sweden and the United Kingdom. Baseline and follow-up data were analysed using bivariate and multivariate logistic regression.
Results: The occurrence of suicidal ideation in the participating countries varied between 6% and 24%. Factors significantly (p < 0.0018) associated with suicidal ideation using bivariate analysis were: nationality, depressive symptoms, delusions, hallucinations, agitation, anxiety, apathy, disinhibition, irritability, night-time behaviour disturbances, anxiolytics and anti-dementia medication. In the multivariate regression analysis, country of origin, moderate stage of the dementia, depressive and delusional symptoms, and anti-dementia medication were significantly associated with suicidal ideation (p < 0.05). Over time, suicidal ideation decreased from severe to mild or became absent in 54% of the persons with dementia.
Conclusion: It is essential that professionals identify older persons with dementia and suicidal ideation and depressive and other psychological symptoms in order to give them appropriate treatment and provide relief for their informal caregivers. We emphasize the importance of identifying suicidal ideation, irrespective of depressive symptoms, and specifically of paying attention to persons with moderate dementia. Living with the informal caregiver seems to be associated with staying stable without suicidal ideation.